Orla lagunar de Maceió : apropriação e paisagem (1960-2009). - Duarte, Rubens de Oliveira (2010)
The lagoon coast area in Maceio city has been changing significantly regarding to the original landscape since the beginning of the century XX. This area itself extends for approximately 24km from the neighborhood called Pontal da Barra to Rio Novo. The main site consider into this research is a fragment of this area and it corresponds physically by an urban road which border the neighborhood of Levada, Ponta Grossa, Vergel do Lago and Trapiche da Barra, as known as Dique-Estrada or simply lagoon coast. This research focuses on the lagoon coast landscape s transformation between 1960 and 2009 and its implications for the site, investigating the site s appropriation for its inhabitants. The methodological procedures for data collection and analysis were based on a bibliographic revision, journals collections, photographic and registers and inhabitant s interviews. As a result, it is possible to identify that a planned site s appropriation happened during the 70 s decade with Dique-Estrada Project implantation. However, from this decade until recently this appropriation have been changing for a more spontaneous and not formal planned way from its inhabitants along with isolated governmental actions. As a consequence, the lagoon coast was consolidated as an area where serious social issues and low development levels demarcated significantly its landscape.